ANALISA PREDIKSI ANGKA KESEMBUHAN COVID-19 PADA BULAN APRIL 2021 - Rio, Firstan; Michael; Charlitos, Ralfpiere; Sudiono; Thang, Susanti (Journal of Digital Ecosystem for Natural Sustainability, 2021)
This study aims to prediction the number of people confirmed recovered COVID-19 from April 16 2021 to April 30 2021. Quantitative methods were used in this study with data sources derived from secondary data and using Simple linear regression analysis methods. Simple linear regression analysis method selection is considered appropriate as a tool to process data in the form of time series such as the data used in this study. The results showed the number of people who confirmed recovered COVID-19 from April 16 2021 to April 30 2021 as many as 142 people.